THE HISTORY OF KAMPONG MADRAS DEVELOPMENT IN MEDAN - Kurniawan, Adam (Border: Jurnal Arsitektur, 2020)
As one of the largest cities in Indonesia, Medan is one of the multiethnic cities that has demographics of residents with different cultural and religious backgrounds. The development of Medan as the best tobacco leaf producing center in the Dutch Colonial period is inseparable from the establishment of Kampong Madras as a residential area of Tamil community. Over time, Kampong Madras began to develop and change the function and physical function of the area. Based on the above phenomenon, research on Kampong Madras area uses a qualitative method by taking research data through a comparison of regional conditions in the Dutch Colonial period and currently by reviewing several related literature studies so that there is a relationship between users, activities, and space in the residential area. The results of the study of Kampong Madras area found that changes related to social, cultural, economic factors related to the development of facilities and infrastructure in Kampong Madras area.